Dual tension band technique for patellar fractures involving articular surface and inferior pole: a retrospective cohort study and finite element analysis - Yanchun Gao; Guifa Wu; Hongli Zhu; Kaixin Bian; Di Wu; Haifeng Wei (Frontiers in Bioengineering and Biotechnology)
BackgroundFractures involving the inferior pole of the patella can lead to postoperative patella baja. For comminuted patellar fractures that affect both the articular surface and the inferior pole, we aim to explore a new fixation method that provides reliable internal stabilization while reducing the incidence of patella baja.MethodsWe conducted a finite element biomechanical study and a retrospective cohort clinical study. The finite element analysis compared the “dual tension band” technique to the traditional single tension band method using 3D models of patellar fractures. The clinical study included 66 patients with patellar fractures involving the articular surface and inferior pole, divided into two groups based on the fixation method. Outcomes were assessed using a range of motion (ROM), Böstman scores, and the Insall-Salvati Index (ISI).ResultsThe finite element analysis revealed that the dual tension band technique resulted in lower maximum stress on the patella and lower displacement on the fixation devices compared to the single tension band. Clinically, patients treated with the dual tension band had significantly higher postoperative ISI values (0.93 ± 0.16 vs. 0.85 ± 0.17, p < 0.05), better ROM (123.75 ± 9.58 vs. 117.63 ± 12.28, p < 0.05), and a lower incidence of patella baja (17.86% vs. 34.21%). The Böstman scores showed no significant difference between the groups.ConclusionThe dual tension band technique provides effective stabilization for patellar fractures involving the articular surface and inferior pole, reducing the incidence of postoperative patella baja and improving functional outcomes.